Influence of heterogeneously deformed quantum heterogeneity point is a matrix for quantum-dimensional states of charges - Pelyashchak, R. M.; Kulyk, N. Ya. (Physics and Chemistry of Solid State, 2015)
Taking into account the equilibrium of mechanical equilibrium, the theory of perturbation of the form of the tensile heterogeneity "quantum dot-matrix" was developed. Within the framework of the deformation potential model, taking into account the perturbation of the surface of the quantum dot, the influence of the inhomogeneously deformed heterogeneity of the "quantum dot matrix" on the quantum states of charges localized inside the quantum dot is theoretically analyzed.